The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5812/ijp-127158
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Zinc are Interlinked But Affected by Different Growth Factors in Iranian Children and Adolescents: Vitamin D and Zinc in Iranian Children and Adolescents

Abstract: Background: Zinc and vitamin D are essential factors required for growth. Recently, studies have shown a possible link between serum zinc and vitamin D levels. Objectives: This study was designed to evaluate this link and its possible affecting growth factors in children and adolescents in Iran. Methods: This cross-sectional study was performed on the data obtained from children aged 2 to 18 years old referring to a growth assessment clinic for routine growth follow-ups in the city of Shiraz from April to Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although a direct relationship between zinc status and undernutrition was concluded by the majority of studies (12 of 20 accounting for 72,537 participants; Figure 4B), the results from reports on overnutrition were more contradictory. While 4 studies concluded direct associations between zinc levels and BMI 42 59-61 , 2 found inverse relationships 62 63 and 6 studies, accounting for 13,440 participants in 4 countries (3 from Iran [64][65][66] , and 1 from Colombia 67 , Australia 68 , and China 69 ), concluded no association between zinc status and overweight (Figure 4B). Among the studies reporting direct associations with both under-and overnutrition was an exceptionally large population study from China with >64,000 participants 42 62 .…”
Section: Associations Between Zinc and Weight Statusmentioning
confidence: 99%
“…Although a direct relationship between zinc status and undernutrition was concluded by the majority of studies (12 of 20 accounting for 72,537 participants; Figure 4B), the results from reports on overnutrition were more contradictory. While 4 studies concluded direct associations between zinc levels and BMI 42 59-61 , 2 found inverse relationships 62 63 and 6 studies, accounting for 13,440 participants in 4 countries (3 from Iran [64][65][66] , and 1 from Colombia 67 , Australia 68 , and China 69 ), concluded no association between zinc status and overweight (Figure 4B). Among the studies reporting direct associations with both under-and overnutrition was an exceptionally large population study from China with >64,000 participants 42 62 .…”
Section: Associations Between Zinc and Weight Statusmentioning
confidence: 99%
“…Although a direct relationship between zinc status and undernutrition was concluded by the majority of studies (12 of 20 accounting for 72 537 participants; figure 4B), the results from reports on overnutrition were more contradictory. While four studies concluded direct associations between zinc levels and BMI, 42 61 66 67 two found inverse relationships 68 69 and six studies, accounting for 13 440 participants in four countries (three from Iran, [70][71][72] and one from Colombia, 73 Australia 74 and China 75 ), concluded no association between zinc status and overweight (figure 4B). Among the studies reporting direct associations with both undernutrition and overnutrition was an exceptionally large population study from China with >64 000 participants.…”
Section: Associations Between Zinc and Weight Statusmentioning
confidence: 99%